Pesca e pobreza no Brasil - Alencar, Carlos Alexandre Gomes de (2014)
This study aims to make an approach on fisheries and poverty issues, which concepts have been used by several authors to present relations between these two issues. There are two contrasting interpretations in the literature on the relationship between fisheries and poverty. The first relates to the view that "they are fishermen, so they are poor". This is the perception of "endemic poverty" which is felt by the fishermen and that, regardless of what they try to do, remain poor. The second interpretation refers to the idea commonly transmitted in that the relationship between fisheries and poverty refers to the distributive role of fishing, or to the fact that fishing (because of its nature of open access) offers a poor livelihood by fishing activity. In other words this is the view that "they are poor, so the fishing is left to them". The socioeconomic profile of Brazilian fishermen for the year 2010, concludes that the Brazilian professional fishermen are mostly artisanal class, which represents 99.14% of the total 824,814 registered professionals. The average age was 39.21 years, with regional and gender differences. Unmarried predominates in the sector, with 49.92% of the total. Most fishermen have incomplete primary education (79.46%) or are either illiterate (6.53%). Informality prevails in the fishing industry with the activity as an individual work or as household economy. This fact is directly related to the character of the artisanal fisheries in Brazil. Furthermore, Brazilian fishermen have been reduced the amount of goods purchased over time, which may be indicative of a deterioration in activity. Regional differences are observed in almost all variables studied RGP. When faced socioeconomic indicators of the Brazilian population, the country may be divided into two groups, the first formed by the North, Northeast and Midwest regions, less developed than the Southeast and South regions. The distribution and concentration of Brazilian fishermen follows this characteristic of the indicators of population while maintaining strong relationship with poverty vulnerability (as more fishermen, more vulnerable) and the IDHM, especially regarding its education component.